SONOMAMMOGRAPHY FOR EVALUATION OF SOLID BREAST MASSES IN YOUNG PATIENTS - Malik, Ghazala; Waqar, Fareesa; Buledi, Ghulam Qadir (Journal of Ayub Medical College Abbottabad, 2006)
Background: This study was carried out to evaluate the applicability of sonomammography as the primary radiological modality in young patients with breast masses. Methods: This study was carried out at Radiology Departments of PNS Shifa Karachi and CMH Rawalpindi from February 2002 to April 2005. Sonomammography of 56 young patients with breast lump was done. Lesions were characterised by using sonographic criteria as benign (n=49), malignant (n=2) and intermediate (n=5) masses. Results of this evaluation were assessed by fine needle aspiration cytology. Results: No false positive result was noted in 49 benign lesions while only one intermediate mass turned out to be malignant. Sensitivity of sonomammography was more for benign 92% than malignant lesions 67%, and its specificity was high for malignant lesions 92.4%. Retrospective scanning was done for intermediate masses. Conclusion: This study proves the efficacy of ultrasound as a method of choice to evaluate breast masses in young patients avoiding the need of biopsy. This study also reflects that benign diseases dominate the disease spectrum in young patients. Keywords: Sonomammography, benign diseases, young patients.